The macroeconomics of scaling up aid : lessons from recent experience - Berg, Andrew...[et al.] (IMF WashingtonUS, 2007)
Identifies and analyzes some of the key macroeconomic issues that arise in connection with high levels of aid inflows. Focuses on developing a framework that will aid economists in studying the policy questions that arise from the scaling up of aid. Applies the framework to five countries that experienced large inflows in recent times.